ANALISIS KOMPETENSI SOSIAL GURU MATA PELAJARAN KIMIA DI SMA NEGERI 9 SEMARANG - Setyani Setyani; Eko Yuliyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The process of teaching and learning is a core of the educational process with the teacher as the primary role holder. The teacher as a person who transfering knowledge to someone or a group of people must have special skills, knowledge, abilities and can carry out required tasks and its role in professional in their job as a teacher and educators. The purpose of this research is to know the social of competence chemistry teacher in SMA Negeri 9 Semarang. The method of research used the qualitative descriptive method with a detailed questionnaire data capture techniques, observation, interviews, and documentation. Analysis of the results of the research competence of social chemistry teacher at SMA Negeri 9 Semarang  showed that the chemistry teacher had a good social competencies. Teachers are already carrying out communication manners, empathetic, and effective; appreciate the students, teachers, and schools; being able to use information and communication technology functionally; able to demonstrate a mature private and goodattitude, and have a work ethic, high responsibility, and have a sense of pride in being a teacher. Keywords :Social Competence, Quantitative, Chemistry Teacher, Students